Re-examination of price level differentials using economic freedom index. Issue 6 (17th August 2016) - Shaar, Karam; Ariff, Mohamed
Abstract : Findings reported in this paper provide improved explanation as to what factors are correlated with price levels across a large sample of 152 countries. The results are obtained from using a new set of variables called economic freedom indices, covering 19 years. Prior studies used income, trade openness, and productivity, which led to results with much less explanatory power compared to findings reported in this paper. We apply advanced panel data econometrics to obtain robust estimates of parameters, which, in our view, led to results with substantially high coefficient of variations close to 90%. The findings show that all the nine dimensions of economic freedom used in this study significantly account for the variations in national price levels.